Sustainability of tilapia production systems - David, Luiz Henrique Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Numerous systems, models, and production techniques have been developed to minimize the environmental impact of aquaculture and make this activity more sustainable. In this context, the thesis aims at developing and investigating sustainable production systems for tilapia farming in Brazil. The thesis comprises eight chapters. Chapter 1 brings a brief theoretical background, the research objectives and thesis approach and outline. Chapter 2 reviews the standards, potentialities, deficiencies, and applications of the emergy method in the sustainability assessment of aquaculture production systems. In this chapter, we also discuss and propose improvements on the emergy synthesis for measuring aquaculture sustainability. In Chapter 3 and 4, the sustainability of commercial tilapia production in aquaponics and biofloc-based systems were evaluated, respectively, using emergy synthesis. We also indicate alternative management to reduce systems’ issues and boost the sustainability of them. An innovative way to account for ecosystem services and disservices within emergy synthesis is proposed and discussed in Chapter 3 to accurately capture the environmental performance for aquaponics systems. The findings presented in Chapter 3 and 4 suggest that aquaponics and biofloc are systems potentially sustainable for tilapia farming in Brazil. However, improvements should be done in both food production systems to improve their sustainable performance. Chapter 5 and 6 investigate the technical feasibility of reducing the amount of feed in periphyton-based systems to produce tilapia in ponds and cages located in a farm dam. The tilapia growth performance presented in Chapter 5 indicates that the proposed production models are promising strategies for using natural food in a periphyton-based system and reusing effluents from monocultures. On the other hand, Chapter 6 shows that rearing tilapia in a farm dam with water poor in nutrients result in low availability of the periphyton and, consequently, the tilapia under feed restriction could not take advantage of the periphyton as natural food. In the study presented in Chapter 7, we show the consumer preferences and perceptions regarding the market for sustainable/certified aquaculture products in Brazil. As the main result of Chapter 7, we found that most Brazilian fish consumers are aware of what certification is and the aspects involved in it. In general, the set of information and findings presented in this thesis can be considered as an important step to support the development of public policies and certification programs to make aquaculture a more sustainable activity.

Inúmeros sistemas, modelos, e técnicas de produção tem sido desenvolvidas para minimizar o impacto ambiental da aquicultura e fazer essa atividade mais sustentável. Nesse contexto, essa tese tem como objetivo desenvolver e investigar sistemas sustentáveis para produção de tilápia no Brasil. A tese é composta de oito capítulos. O Capítulo 1 compreende um breve embasamento teórico, os objetivos e a abordagem da tese. O Capítulo 2 analisa os padrões, potencialidades, deficiências e aplicações da síntese em emergia na avaliação da sustentabilidade dos sistemas de produção de aquicultura. Neste capítulo, também discutimos e propomos melhorias na síntese em emergia para medir a sustentabilidade da aquicultura. Nos Capítulos 3 e 4, a sustentabilidade da produção comercial de tilápia em sistemas aquapônicos e baseados em bioflocos foi avaliada usando síntese em emergia. Também indicamos uma gestão alternativa para reduzir os problemas dos sistemas e aumentar a sustentabilidade dos mesmos. Uma maneira inovadora de contabilizar os serviços e desserviços do ecossistema na síntese em emergia é proposta e discutida no Capítulo 3 para medir com precisão o desempenho ambiental dos sistemas aquapônicos. Os resultados apresentados nos Capítulos 3 e 4 sugerem que a aquaponia e o bioflocos são sistemas potencialmente sustentáveis para a criação de tilápia no Brasil. No entanto, melhorias devem ser feitas em ambos os sistemas de produção para melhorar seu desempenho sustentável. Os Capítulos 5 e 6 investigam a viabilidade técnica de reduzir a quantidade de ração em sistemas baseados em perifíton para produzir tilápia em viveiros e em tanques-rede alocados em pequenos reservatórios. O desempenho do crescimento da tilápia apresentado no Capítulo 5 indica que os modelos de produção propostos são estratégias promissoras para o uso de alimentos naturais em um sistema baseado em perifíton e reutilização de efluentes de monoculturas. Por outro lado, o Capítulo 6 mostra que a criação de tilápia em pequeno reservatório com água pobre em nutrientes resulta em baixa disponibilidade do perifíton e, consequentemente, a tilápia sob restrição alimentar não poderia aproveitar o perifíton como alimento natural. No estudo apresentado no Capítulo 7, mostramos as preferências e percepções dos consumidores em relação ao mercado de produtos aquícolas sustentáveis / certificados no Brasil. Como resultado principal do Capítulo 7, descobrimos que a maioria dos consumidores brasileiros de pescado está ciente do que é certificação e dos aspectos envolvidos nela. De maneira geral, o conjunto de informações e resultados apresentados nesta tese pode ser considerado um passo importante para apoiar o desenvolvimento de políticas públicas e programas de certificação que tornem a aqüicultura uma atividade mais sustentável.
Sustentabilidade dos sistemas de produção de tilápia
Keywords: Ponds; Tilápia; Ecosystems